Partial inferior turbinectomy versus submucosal diathermy in hypertrophied inferior turbinates - Gangaraj, Smitha S.; Thomas, Shilpa (International Journal of Otorhinolaryngology and Head and Neck Surgery, 2020)
Background: The study aims to compare the efficacy of submucosal diathermy and partial inferior turbinectomy in terms of improvement in nasal obstruction, pain, haemorrhage, crusting and wound healing. Methods: A prospective sequentially randomized comparative study involving fifty patients, divided into two groups of 25 patients each. Group A consists of patients who underwent SMD and group B consists of patients who underwent PIT. Post-operative assessment was done at day 1, 2 weeks, 1 month, 3 months and 6 months. Results: Post-operative improvement in nasal obstruction was seen in both groups. 80% showed significant improvement in SMD and 32% in PIT group at the end of second week. By sixth month, 40% in SMD group and 80% in PIT group showed significant improvement. Mild pain was observed in 12% of PIT group at 2 weeks. In SMD group, 8% developed reactionary haemorrhage. In PIT group, 24% developed minimal soakage and 12% developed moderate soakage. Severe nasal crusting was seen in 64% of the cases in PIT group and in 40% of the cases in SMD group at second week. By 1 month, 44% in PIT group and 12% in SMD group showed severe crusting. Conclusions: Short term complications like pain, obstruction and haemorrhage was noted to be higher with PIT. On long term evaluation, PIT showed better results in terms of improvement in nasal obstruction scores.